A The Role of Self Control as a Moderating Variable on The Effect of Financial Inclusion on Financial Behavior - Ardiana, Meta; Agustina, Rachma; Pertiwi, Dwi (Jurnal Economic Resource, 2024)
Financial behavior among the public is still low, based on research conducted by the OCBC Financial Index showing data that the financial literacy and behavior index of the younger generation is still in the low range category, namely 37.72 out of 100 in 2021 for 1,027 respondents. Previous research on "financial behavior" that was carried out by Perry and Moris (2005) suggests that there are three factors that can affect "financial behavior" including: first one's self-control over whatever happens in life or also called (locus of control). Second, one's financial knowledge of matters related to money or banking products. Third, the level of one's income or (income). Research Objectives: to provide empirical evidence of the effect of financial inclusion on financial behavior. This research was conducted on students of the Faculty of Economics, Hasyim Asy'ari University with a total population of 980 students with sample calculations using the slovin formula. Research Methods using quantitative research methods with Smart PLS. The results of the hypothesis analysis show that the results of financial inclusion influence financial behavior. And Self Control can moderate or strengthen the relationship of financial inclusion to financial behavior.